National Evaluation of the Safe Start Promising Approaches Initiative, 2006-2010 - Jaycox, Lisa H. ([Verlag nicht ermittelbar], 2013)
The Safe Start Promising Approaches for Children Exposed to Violence Initiative funded 15 sites to implement and evaluate programs to improve outcomes for children exposed to violence. RAND conducted the national evaluation of these programs, in collaboration with the sites and a national evaluation team, to focus on child-level outcomes. The dataset includes data gathered at the individual family-level at baseline, 6-, 12-, 18-, and 24-months. All families were engaged in experimental or quasi-experimental studies comparing the Safe Start intervention to enhanced services-as-usual, alternative services, a wait-list control group, or a comparable comparison group of families that did not receive Safe Start services. Data sources for the outcome evaluation were primary caregiver interviews, child interviews (for ages 3 and over), and family/child-level service utilization data provided by the Safe Start program staff.